Rice growth under water stress levels imposed at distinct developmental stages - Parfitt, José Maria Barbat (2019)
We aimed to assess rice growth as function of water stress at distinct crop stages, under greenhouse, using randomized block design and factorial scheme 3 × 4 + 1, with four replications. Factor A was the growth stage when water stress was imposed, being (1) vegetative, (2) reproductive 1, and (3) reproductive 2; factor B was four levels of water stress (0 ‑ 200 kPa). The additional treatment consisted of a flooded check. Water was replenished to saturation every time the threshold stress was reached. Rice height is reduced when stress is applied either at vegetative or reproductive stages; tillering was affected only by water stress at the vegetative stage, and plants did not recover after the stress was withdrawn; surplus in leaf area is likely to help recovering plant performance from stress applied at the vegetative stage; water content was not affected by water stress, but shoot dry mass of culms was reduced with stress between tillering start and anthesis; root volume did not increase as function of water stress at the vegetative stage. Rice growth is little affected by the absence of waterlogging, but stress levels should be below 30 kPa throughout cropping cycle.